Leptin mediates protective effects on the vasculature. (3rd October 2022) - Filipova, V; Stuerzebecher, P E; Kralisch, S; Schubert, M R; Hoffmann, A; Oliveira, F; Sheikh, B; Blueher, M; Kogel, A; Scholz, M; Miehle, K; Ebert, T; et al.
Abstract: Introduction and purpose: Lipodystrophy (LD) syndromes are characterized by the loss of adipose tissue resulting in metabolic complications and accelerated atherosclerosis. The systemic concentration of the adipokine leptin is reduced in LD as a result of adipose tissue deficiency. A therapeutical option to treat LD is the substitution of leptin, which improves metabolic complications and reduces mortality. However, the vascular effects of leptin remain largely unknown. Here we analyze the direct effects of leptin on the vascular system and the development of atherosclerosis. Methods and results: Treatment of human endothelial cells (ECs) with leptin reduced endothelial inflammation and the process of endothelial-to-mesenchymal transition (EndMT) (CNN1, −41.4%, p<0.05, n=4). In addition, leptin administration prevented the EndMT-induced increase of endothelial permeability. The protective effect of leptin on EndMT was confirmed in vivo in a combined lipodystrophic and atherosclerosis-prone mouse model (LDLR−/−; aP2-nSrebp1c). Treatment of the mice with leptin (3.0 mg/kg body weight daily for 8 weeks) decreased EndMT. Leptin showed no effect on plaques size but reduced the protrusion of plaques in atherosclerotic areas of the aortic roots (−31%, p<0.05, n=4–6). Cytokine screening revealed an increase of the growth differentiation factor 15 (GDF15) in serum of LD patients (+26.2%, p<0.05, n=53–58) and in ECs after EndMT (+138%, p<0.05, n=6743–10920). This increase was reversed using leptin treatment in ECs undergoing EndMT, in the LD mice model, and in LD patients after 4 weeks of leptin administration. Indeed, treatment of endothelial cells with GDF15 induced EndMT (CNN1, +7.7-fold-control, p<0.05, n=3), and impaired EC barrier function. Neutralizing antibodies targeting GDF15 inhibited EndMT-mediated expression of mesenchymal genes (CNN1, −54%, p<0.05, n=4). The treatment of ECs with serum from LD patients induced EndMT and the increase of mesenchymal marker expression was inhibited with additional administration with neutralizing antibodies targeting GDF15 (CNN1, −28%, p<0.05, n=3). Conclusion: Our findings indicate that EndMT is part of the cardiovascular disease progression in lipodystrophy syndromes. Leptin treatment has direct protective vascular effects by preventing inflammation, EndMT, and maintaining endothelial integrity. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation)